FRI0471 A comparative analysis of erosion repair in rheumatoid arthritis (RA) patients by magnetic resonance imaging (MRI) and hr-pqct. (23rd January 2014) - Regensburger, A.; Koch, P.; Kraus, S.; Hecht, C.; Englbrecht, M.; Rech, J.; Schett, G.; Faustini, F.; Finzel, S.
Abstract : Background: The detection of bone erosions is fundamental both for monitoring of disease activity and therapy decisions in rheumatoid arthritis (RA). Recently, it could be shown by high-resolution peripheral quantitative computed tomography (HR-pQCT) that erosion repair is associated with bone apposition at the bottom of the erosion ("sclerosis") [1 ;2 ]. MRI however is more widely available in clinical settings and used as a monitoring tool of disease activity in RA. Objectives: To investigate whether MRI allows visualization of sclerosis at the bottom of erosive lesions in comparison to HR-pQCT as a reference. Methods: 53 RA patients fulfilling the new ACR/EULAR criteria received a 1.5T MRI (Siemens, Vario) and an HR-pQCT (Scanco Medical AG, XtremeCT) of the metacarpophalangeal joints 2 and 3 of the clinically dominant hand. Prevalence of erosions as well as sclerosis was assessed in both imaging modalities in the coronal plane. All MRI- and CT-images were evaluated twice by two readers in a blinded fashion. Demographic and clinical data were collected for each patient. Results: 69.8% of patients were females, mean ±SD age was 53.15±15.90 years; mean disease duration ±SD was 34.9±64.5 months, and mean DAS28±SD was 3.61±1.81. Prevalence of RF and ACPA was 52.8% and 58.5% respectively. A mean number of 66.5 erosions were detected by MRI per reading as compared to 81.5 erosions per reading by HR-pQCT (4 readings, 2 readers for each modality). The average proportion of correctly classified non sclerosed lesions in the MRI compared to HR-pQCT was 94% (specificity), while the average proportion of correctly classified sclerosed lesions was 31% (sensitivity). Hence, our results show a good concordance of the two imaging modalities for absence of sclerosis, but poor agreement for presence of sclerosis. On average, the observation of a "non sclerosed lesion" in the MRI was correct in 80.5% of cases after validation by HR-pQCT (negative predictive value-NPV), whereas it was 62% for "sclerosed lesions" in the MRI (positive predictive value-PPV). Conclusions: According to our results, MRI has limitations to detect repair of bone lesions in RA. References: Finzel S, Rech J, Schmidt S, et al. Ann Rheum Dis. 2011 Sep;70(9):1587-93. Finzel S, Rech J, Schmidt S, et al. Ann Rheum Dis. 2012 May 14. [Epub ahead of print] Disclosure of Interest: None Declared